Influence of 16S rRNA target region on the outcome of microbiome studies in soil and saliva samples - Soriano-Lerma, Ana (Sci Rep, 2020)
Next generation sequencing methods are widely used in evaluating the structure and functioning of microbial communities, especially those centered on 16S rRNA subunit. Since Illumina Miseq, the most used sequencing platform, does not allow the full sequencing of 16S rRNA gene, this study aims to evaluate whether the choice of different target regions might affect the outcome of microbiome studies regarding soil and saliva samples. V1V3, V3V4, V4V5 and V6V8 domains were studied, finding that while some regions showed differences in the detection of certain bacterial taxa and in the calculation of alpha diversity, especially in soil samples, the overall effect did not compromise the differentiation of any sample type in terms of taxonomic analysis at the genus level. 16S rRNA target regions did affect the detection of specific bacteria related to soil quality and development, and microbial genera used as health biomarkers in saliva. V1V3 region showed the closest similarity to internal sequencing control mock community B, suggesting it might be the most preferable choice regarding data reliability.